2006
DOI: 10.1074/jbc.m510692200
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides from Burkholderia cenocepacia Inhibit Neutrophil Chemotaxis and Scavenge Reactive Oxygen Species

Abstract: Bacteria belonging to the Burkholderia cepacia complex are important opportunistic pathogens in compromised hosts, particularly patients with cystic fibrosis or chronic granulomatous disease. Isolates of B. cepacia complex may produce large amounts of exopolysaccharides (EPS) that endow the bacteria with a mucoid phenotype and appear to facilitate bacterial persistence during infection. We showed that EPS from a clinical B. cenocepacia isolate interfered with the function of human neutrophils in vitro; it inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 50 publications
2
83
2
Order By: Relevance
“…in human airways is suggested by its capacity to scavenge reactive oxygen species and inhibit neutrophil chemotaxis (Bylund et al, 2006). In our study, EPS biosynthesis did not correlate with the ability to cause onion rot, which is perhaps to be expected since pectinases rather than EPS are likely to play the major role in the maceration of plant tissue.…”
Section: Discussionmentioning
confidence: 48%
“…in human airways is suggested by its capacity to scavenge reactive oxygen species and inhibit neutrophil chemotaxis (Bylund et al, 2006). In our study, EPS biosynthesis did not correlate with the ability to cause onion rot, which is perhaps to be expected since pectinases rather than EPS are likely to play the major role in the maceration of plant tissue.…”
Section: Discussionmentioning
confidence: 48%
“…QS-molecules also stimulate phagocytosis, where the stimulation is concentration-dependent. In proximity to biofilms the concentrations of the molecules are high which leads to an inhibition of chemotaxis and phagocytosis in the immune cells, protecting the bacteria from elimination [5,6].…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%
“…The most common EPS produced by members of the BCC is cepacian (Herasimenka et al, 2007), the biosynthetic enzymes for which are encoded by the bce-I and bce-II gene clusters (Moreira et al, 2003;Ferreira et al, 2010). Whilst EPS has been identified as a putative virulence factor within the BCC (Conway et al, 2004;Cunha et al, 2004;Bylund et al, 2006), it has been reported that an inverse correlation exists between the amount of EPS produced and the rate of lung function decline in CF patients, with the presence of nonmucoid isolates linked to the greatest decline in the patients studied (Zlosnik et al, 2011). However, the precise role played by EPS during infection of the CF lung remains unclear, and direct evidence for EPS production by BCC within the lung is currently lacking.…”
Section: Introductionmentioning
confidence: 99%